Management practices, productive performances and egg quality traits of exotic chickens under village production system in east Shewa, Ethiopia - Tadesse, D.T. (Addis Ababa University, 2012)
A cross sectional study was conducted with the objectives of assessing management practices, evaluate productive performance and egg quality traits of Isa Brown (IB), Bovan Brown (BB) and Potchefstroom Koekoek (PK) under village production system, from November 2011 to May 2012 in Ada’a and Lume districts of East Shewa, Ethiopia. Totally, 180 randomly selected respondents were included in the study from six purposively selected Peasant Associations (PAs) from two districts. The data collected were analyzed using SPSS version 17. In both districts, 97.8% of the respondents provided additional supplement. Over 95% of the respondents used maize and wheat as additional supplements, mostly three times a day. About 96% of respondents in both districts provided water with free access. The 80 % in Ada’a and 71.2% respondents in Lume districts had good market access to procure poultry production inputs and 68.8% in Ada’a and 94.4% respondents in Lume had good market access to sell eggs and chicken. Extension services were used by 41.2% in Ada’a and 53.4% respondents in Lume districts. The 78.8% of respondents did not vaccinate their chicken, in Ada’a, whereas 80% of respondents vaccinate their chicken in Lume districts. Collectively, about 56% of the respondents provided Oxy-tetracycline 20% as prophylactic measures against various poultry diseases. The average eggs laid/year/bird was 276.1, 266.32, and 178.07 eggs for IB, BB and PK, respectively. Average age at first laying was 160.5, 165.5 and 153 days for IB, BB and PK respectively. BB was superior for egg weight, yolk height, albumin height, albumin weight, Haugh Unit and eggshell thickness than IB and PK. IB was found to be superior to BB and PK for yolk weight, whereas PK was superior to IB and BB for yolk colour. Diseases, in adequate veterinary services, feed shortage and predators were listed as major constraints in both districts. Getting improved chicks at affordable price, provision of vaccination, training on poultry rearing, supply of electricity and clean water were mentioned as option to improve chicken productivity in the study areas. In this study, the performance of hybrid layers seems to be over reported by farmers and this requires further study considering the amount of additional feed supplement by farmers’ and proper recording on the number of eggs to better conclude on their productive performances.